Can Finance Save the World? : Regaining Power over Money to Serve the Common Good. - Badré, Bertrand (Berrett-Koehler Publishers, Incorporated, 2018)
"How to Make Finance a Force for Good Just as Thomas Piketty offered a sweeping critique and progressive reassessment of capitalism, former World Bank Group chief financial officer Bertrand Badre looks at the destructive role finance played in the global economic crisis of 2007-2008 and offers a bold prescription for making it a force for good. Badre describes how finance can be harnessed to help us solve many of the world's biggest problems--climate change, poverty, infrastructure rebuilding, and more. As he writes, "When controlled and used intelligently, with benevolence and inventiveness, finance can accomplish great things.""--